FRAGMENTS OF A SECOND AVAR HORSE DISCOVERED IN SÂNCRAIU DE MUREȘ AN ARCHAEOZOOLOGICAL REPORT - Alexandru GUDEA; Călin COSMA; Cristian MARTONOS (Journal of Ancient History and Archaeology, 2023)
The material presented was in a decent state of conservation, allowing, in most cases, only partial measurements. The material belonged to one single horse (Equus caballus), which was evaluated from an anatomical perspective and an osteometrical as well. According to the concluded data, the bones belonged to a young individual, no more than 2-2.5 years old, with an average height calculated, based on the measured long bones, of 135 cm. The gracility indices point to a medium- slender individual. Comparative data from a few Avar period discoveries in the territory of Romania, Hungary and Croatia allow a much larger perspective on the morphology of the identified individuals.